Caregiver Quality of Life and Daily Functioning in Relation to Ventilating Tube Treatment. (14th April 2014) - Heidemann, Christian Hamilton; Lauridsen, Henrik Hein; Kjeldsen, Anette Drøhse; Faber, Christian Emil; Johansen, Eva Charlotte Jung; Godballe, Christian
Abstract : Objective: Caregiver quality of life and daily functioning may improve after ventilating tube treatment in children with otitis media. The aims of this study are to assess possible changes in caregiver quality of life and daily functioning in relation to ventilating tube treatment and to investigate possible predictors for clinical success. Study Design: Longitudinal observational study. Setting: Secondary care units. Methods: Four hundred ninety‐one families were enrolled in the study. The Caregiver Impact Questionnaire was applied in the assessment of caregiver quality of life. Caregivers completed questionnaires at baseline and at 1, 3, 6, 12, and 18 months' follow‐up. Variables on caregiver daily functioning comprised 4 weeks' history of number of interrupted nights, absenteeism, cancelled social activities, and doctor visits as a result of otitis media in the child. Results: Response rates ranged from 96% to 79%. Significant improvements in disease‐specific quality of life were seen after treatment. The poorest baseline quality of life was found in caregivers of children with recurrent acute otitis media. Significant improvements were found on all variables on daily functioning. Predictors for caregiver‐perceived clinical success included child sex, number of interrupted nights, doctor visits, absenteeism, and cancelled social activities. Conclusion: Results of this study support the notion that caregivers of children with otitis media with defined surgical indications improve their quality of life and daily functioning after ventilating tube treatment. Factors related to caregiver functioning and disease severity were found to be associated with caregivers experiencing important improvements after treatment.